Analysis Capacity And Cost Tool Heavy To Production Work (Study Case : Building Construction New SMAN 2 Bukittinggi) - Prasetya Yoanda, Bima; Abdullah, Rijal (Greenation International Journal of Engineering Science, 2023)
In the implementation of quality work work very needed And will reflect production Work That alone. However, in the Building Construction project New SMAN 2 Bukittinggi does not use heavy equipment properly what have planned. Heavy equipment used produce low production so that raises impact negative for results production And cost on implementation project That alone. After do analysis calculation about capacity And cost usage tool heavy on building construction project New SMAN 2 Bukittinggi this, for can finish work in accordance with those who have planned on project, must know capacity productive in the field. Because with know capacity productivity in the field, will easy determine work in accordance with capacity And the cost. The need use capacity more production big on tool heavy, will determine production quality work.